2009
DOI: 10.1002/pssc.200881007
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic transitions in silicon nanostructures probed by time‐resolved photoluminescence spectroscopy

Abstract: Time‐resolved photoluminescence spectroscopy has been utilized to reveal excitonic transitions in silicon nanowires and silicon nanocrystals. While previous works on porous silicon and silicon nanocrystals have shown a two‐level splitting, e.g., singlet‐triplet states, our measurements reveal the fine structure of the excitons including three semi‐bright states and a ground dark excitonic state. Surprisingly, for silicon nanowires we have found the slowest semi‐dark exciton to fall above the faster semi‐bright… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…However, passivation of the surface of the SiNWs with an oxide layer will lead to a decreased density of DT states, resulting in a net decrease in trap state PL intensity. Nevertheless, the PL that is observed (modeled in Figure ) is believed to arise from the recombination from the Si/SiO 2 interface states, which act as DTs, for which this assignment has been made before. , SiNW samples with lower relative porosity will thus have low overall PL, yet will exhibit characteristic SiO 2 peaks (Figure ).…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…However, passivation of the surface of the SiNWs with an oxide layer will lead to a decreased density of DT states, resulting in a net decrease in trap state PL intensity. Nevertheless, the PL that is observed (modeled in Figure ) is believed to arise from the recombination from the Si/SiO 2 interface states, which act as DTs, for which this assignment has been made before. , SiNW samples with lower relative porosity will thus have low overall PL, yet will exhibit characteristic SiO 2 peaks (Figure ).…”
mentioning
confidence: 79%
“…Bulk silicon is known to be an indirect bandgap semiconductor with weak PL. Because of this, quantum confinement effects are thought to be the cause of PL in silicon nanocrystals. Surface effects have also been suggested to play an important role in the PL of nanostructured Si. For instance, cathode luminescence and time-resolved PL spectroscopy have shown that luminescence in silicon nanowires (SiNWs) is due to interface states and surface radiative recombination centers located at the interface of the silicon core and the SiO 2 cladding layer. , …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, for the electrical systems, the “sluggishness” in manifested by a characteristic time constant τ of the rise and/or the decay of σ(t) which is much longer than any experimental macroscopic or intrinsic microscopic time of the system such as carrier scattering or recombination times [ 20 ] (which are less than a msec. in Si NCs [ 39 , 40 ]).…”
Section: Introductionmentioning
confidence: 99%